2001
DOI: 10.1016/s0033-3506(01)00446-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the use of breast and cervical cancer screening services among Chinese women in Hong Kong

Abstract: We conducted a cross-sectional survey using a self-administered questionnaire among attendees of a well women clinic in Hong Kong during June and July 1998. The study aimed to examine the factors associated with the past and future use of screening services among Chinese women in Hong Kong and their perception of service providers. Of the 430 respondents (64% response rate), 87% were aged 31-50 y, 85% married, 93% attained education to upper secondary school level, and 96% were non-smokers. Nearly all responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 0 publications
4
19
1
Order By: Relevance
“…Consistent with Abdullah and Leung's study [20], the present study also found that a positive perception of health behaviors (e.g., a balanced diet and visiting a doctor regularly) was associated with previous screening experience. This indicated that respondents with past screening experience are more likely to come for screening because of their cultural family obligations and personal health beliefs and practices.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…Consistent with Abdullah and Leung's study [20], the present study also found that a positive perception of health behaviors (e.g., a balanced diet and visiting a doctor regularly) was associated with previous screening experience. This indicated that respondents with past screening experience are more likely to come for screening because of their cultural family obligations and personal health beliefs and practices.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…Health consciousness has been suggested as a key component of screening behaviour [13,29,30]. In this study there is a higher screening rate among respondents who have a family history of cancer and those of a higher education level.…”
Section: Discussionmentioning
confidence: 77%
“…The findings of this study have provided important data about the status of breast health awareness of women in Hong Kong. About half of the women we reached were aware of breast health, diseases, BSE, (Abdullah & Leung, 2001;Chua et al, 2005), and studies in the region, such as those in Taiwan and Malaysia (Chee et al, 2003;Lu, 2001 (Health Canada, 2003). Although Hong Kong has no standard guidelines to recommend routine mammography screening to asymptomatic women at the population level (the risk of breast cancer is lower in Hong Kong compared with western populations), a recent report from the Hong Kong Department of Health, Centre for Health Protection (2004) encouraged all women in the general population to be ''breast aware,'' to be alert to the early signs and symptoms of breast cancer, and to seek medical attention as soon as possible so as to reduce the interval between diagnosis and treatment to a minimum.…”
Section: Discussionmentioning
confidence: 99%